Ensino jurídico em São Paulo: desafios da formação - (a experiência da PUC- SP) - Pinto, Daniella Basso Batista (2013)
This research aims to investigate how the formation of future professional law at the University for entry into the labor market, the professionalization process, the role of teachers teaching in the classroom. Therefore, we sought to examine how learning is accomplished legal practitioners, the trajectory of Legal Education in Brazil, which contents are being worked on curriculum subjects and whether they provide knowledge of humanistic slant to the development of meaningful learning, so that students, in their profession, act in society that has undergone significant transformations and changes with regard to social, economic, political, cultural and technological. It was intended to finally prove the importance of integration of the areas of academic knowledge, interdisciplinarity, since it does require a learning focused on social reality in which they live future jurists in order to gain an understanding not only dogmatic and technicist, but an understanding of historical, sociological, psychological, anthropological and philosophical, humanistic training - critical education, liberating education, innovative curriculum, individual, university culture, cultural diversity, pillars of education, interdisciplinarity. In this sense, the research problem was to determine: "How is the Humanistic Education in undergraduate courses in law that arise and identify with innovative curricula in contemporary society?". Regarding methodology, we conducted a literature search based on books and journals with regard to the themes of the research. Moreover, there was also a documentary research and a case study with a qualitative approach and a descriptive and analytical, and, as a methodological procedure, interviews with teachers, lawyers, Pontifical Catholic University of São Paulo - PUC -SP in order to discuss about the tradition, the history and prospects of law school for the Brazilian Legal Education in order to verify the proposed innovative in their curriculum